La satisfacción del cliente de fast-food. Explorando impulsores en personas con malos hábitos alimenticios usando el modelo ACSI - Leyva Rodríguez, Giannela (2023)
The fast-food industry faces constant criticism for encouraging bad eating habits, especially in the young population. In this market, customer satisfaction represents a key determinant for decision making. Despite the extensive literature on customer satisfaction, few studies have focused on exploring the drivers in customers belonging to sensitive or at-risk segments, such as people with poor eating habits. Using the American Customer Satisfaction Index (ACSI) model, a phenomenological and qualitative study was developed through interviews and observation of 18 fast food consumers with marked characteristics of poor eating habits. Our analysis reveals that this group of customers considers the variety and proximity of products, as well as entertainment, ease of purchase and value for money, as drivers of their purchases. At the same time, the empathy and treatment of the staff is seen to consolidate the desire of these consumers. The findings suggest that satisfaction is a retention factor for users with poor nutrition, so new health policies aligned to this sector are required.